1989
DOI: 10.1088/0029-5515/29/2/001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of second harmonic ICRF waves in NBI heated JT-60 plasmas

Abstract: The propagation and absorption of second harmonic ion cyclotron range of frequency (ICRF) waves in NBI heated plasmas are investigated for the regime of plasma parameters in JT-60. The quasi-linear diffusion in the velocity space of ions is taken into account. The Fokker-Planck equation and the kinetic wave equation are numerically solved to obtain the spatial profile of the velocity distribution function and the power deposition profile in a self-consistent manner. The calculation of the power partition rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…However, tail temperatures were almost the same for the third and fourth harmonics. The dependence of the tail temperature on the harmonic number was found to be in qualitative agreement with results from a simulation code analysis based upon the 1-D Fokker-Planck equation coupled with the kinetic wave equation [31]. However, the experimental tendency of the tail ion stored energy showed that the response to the level of absorbed ICRF power is much stronger than the response to the harmonic number.…”
Section: Neutral Particle Analysis In the Megaelectronvolt Rangesupporting
confidence: 76%
“…However, tail temperatures were almost the same for the third and fourth harmonics. The dependence of the tail temperature on the harmonic number was found to be in qualitative agreement with results from a simulation code analysis based upon the 1-D Fokker-Planck equation coupled with the kinetic wave equation [31]. However, the experimental tendency of the tail ion stored energy showed that the response to the level of absorbed ICRF power is much stronger than the response to the harmonic number.…”
Section: Neutral Particle Analysis In the Megaelectronvolt Rangesupporting
confidence: 76%
“…We evaluate the incremental stored energy by beam acceleration, employing a one-dimensional selfconsistent code which takes into account the global wave structure and the quasi-linear velocity space diffusion. Details of the calculation are described in Refs [15,16]. The calculated incremental stored energy of the beam component is about 200 kJ, which is in reasonable agreement with the experiment.…”
Section: Icrf 'supporting
confidence: 72%
“…Anisotropy in velocity space is approximated using formulas suggested by Hammett [34]. The Fokker-Planck equation for the distribution function f is solved in terms of the energy W ; the most important terms in the equation are the beam source, the collisional drag on electrons and thermal ions, and the angle averaged quasi-linear RF diffusion operator [35],…”
Section: Predicted Neutron Enhancementmentioning
confidence: 99%